2005
DOI: 10.4321/s1130-01082005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment in inflammatory bowel disease

Abstract: Aim: adherence to therapy is important to ensure success. We wanted to explore this feature in patients with inflammatory bowel disease. Patients and methods: we explored adherence to treatment and its modifiers in 40 patients with inflammatory bowel disease using a battery of tests. Results: a 67% of patients (95% CI: 51-81%) acknowledged a certain degree of involuntary nonadherence, and 35% (95% CI: 20-51%) of voluntary nonadherence. Overall, 72% (95% CI: 56-85%) of patients had some form of nonadherence. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 21 publications
7
46
0
2
Order By: Relevance
“…Sewitch et al [10] found an increased risk of intentional non-adherence to be associated with being treated by the same physician for more than one year, not scheduling another appointment, and greater total discordance between the patient and the physician. Similarly, a higher degree of intentional non-adherence in the study by López San Román et al [31] was associated with greater patient depression and patient-physician discord. Patients trusted their physician less, and considered themselves to be less informed about their treatment.…”
Section: Patient-doctor Relationshipmentioning
confidence: 86%
“…Sewitch et al [10] found an increased risk of intentional non-adherence to be associated with being treated by the same physician for more than one year, not scheduling another appointment, and greater total discordance between the patient and the physician. Similarly, a higher degree of intentional non-adherence in the study by López San Román et al [31] was associated with greater patient depression and patient-physician discord. Patients trusted their physician less, and considered themselves to be less informed about their treatment.…”
Section: Patient-doctor Relationshipmentioning
confidence: 86%
“…During these visits, routine pill checks can be very helpful through asking the patient to bring in his medication to be inspected by the physician to assess the extent of home utilisation. 29,34 Counselling about the importance of adherence in periods of remissions should be given in the follow-up visits. The major strength of our study lies in the fact that (to our knowledge) this is the first report of nationwide data regarding adherence to mesalazine and the role of adherence in predicting disease flares.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of perceived doctor-patient discordance have also been linked to non-adherence. 44,45 To pursue educational and employment commitments, young adults are often highly mobile and frequently change their treating physician, and it is possible that the absence of a fixed point of contact with an IBD physician leads to more non-adherence. The observation that MMP levels were higher in adults is possibly explained by a combination of better adherence and the fact that the adults in this cohort were more often hypermethylators.…”
mentioning
confidence: 99%